Analisis Potensi yang Mendukung Pertumbuhan Ekonomi di Kabupaten Gowa - Putri, Rini Dwi (Universitas Teuku Umar, 2025)
This study aims to analyze the potential of business sectors that support economic growth in Gowa Regency. This study uses a quantitative approach using GRDP data at constant prices from 2010 for the period 2019–2023. The analysis method used is the Location Quotient (LQ) to identify basic and non-basic sectors. The results show that of the 17 sectors, 7 are classified as basic (e.g., Real Estate, Agriculture, Information and Communication), which contribute significantly to GRDP and have significant potential for job creation. Meanwhile, the remaining 10 sectors are classified as non-basic (e.g., Manufacturing Industry, Construction). Although they have high GRDP values, their low LQ values indicate contributions below the provincial average and require strengthening strategies. These findings recommend prioritizing basic sectors and strengthening non-basic sectors in regional economic development planning.Keywords : GRDP, Basic Sectors, Non-Basic, Economic Growth